PENGARUH PENGGUNA MANFAAT PROGRAM E-COMMERCE SHOPEE AFFILIATES - Devi Kurniawati; Rohmad Abidin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The purpose of this research is to understand how the Shopee affiliate program predictive system works and what benefits and advantages it offers to users and sellers. The impact of the pandemic requires a person or society to be face-to-face with technology to carry out activities virtually or online. As time goes by, people have started to innovate with technological advancements. The first and foremost example is how the world of commerce has grown thanks to e-commerce. E-commerce is part of e-business, where the scope is larger and involves not only trading goods, but also close collaboration with other businesses such as partners, customer service, job vacancies, and others. Affiliate marketing is defined as a cooperative activity that involves partnering with organizations, businesses, or locations to generate profits for both parties involved in a particular transaction through strategies to introduce new products or services. Affiliates, also known as influencers or content creators, are able to influence consumers' desire to make large purchases so that they can drive traffic to their websites and earn commissions. Affiliate with Shopee, on the other hand, is the company's sole affiliate program, aimed at website creators who want to use it to increase commissions by promoting or highlighting products on Shopee through social media. There are many platforms that can be used, ranging from Instagram, YouTube, Facebook, Tiktok, and Twitter. A commission of around 10% is available for each sale made by the promoted shop or product. However, despite how popular this program is, many people in society are unaware of its benefits and drawbacks. As a result, when using e-commerce, not all sellers benefit (profitable income) from the products sold. The current research utilizes the same quantitative method used to develop the full prediction system to build a system. The first step is to collect data from several influential users of the Shopee affiliate program, after which the system development and implementation are carried out. The observation accuracy testing conducted had excellent working conditions with a 100% success rate. Therefore, it can be assumed that the predicted financial benefits and gains from Shopee users will be realized. With this system in place, it is anticipated that consumer spending on Shopee will increase. However, because it is simple and offers the most benefits, this approach may reduce the pentagularity of the population.